Preventing hydrogen sulfide corrosion of sewers - Dąbrowska, Barbara (Instal, 2019)
A discussion concerning methods of sulfate corrosion prevention and protection of concrete sewers are presented. Advantages and shortcomings of these methods were listed. Special attention was paid to prevention.
Keywords: hydrogen sulfate; concrete corrosion; sewerage